2012
DOI: 10.1118/1.3673775
|View full text |Cite
|
Sign up to set email alerts
|

Gap compensation during PET image reconstruction by constrained, total variation minimization

Abstract: A TV minimization strategy incorporated into commonly used PET reconstruction algorithms was useful for reducing the occurrence of artifacts due to gaps between detector modules in small-diameter PET scanners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…1(a). The resultant sinograms were then reconstructed using our image recovery technique (WTV) as well as a simple TV reconstruction similar to the approach of Ahn et al 12 A block diagram of the recovery process is shown in Fig. 1(b).…”
Section: B1 Simulation Studymentioning
confidence: 99%
See 4 more Smart Citations
“…1(a). The resultant sinograms were then reconstructed using our image recovery technique (WTV) as well as a simple TV reconstruction similar to the approach of Ahn et al 12 A block diagram of the recovery process is shown in Fig. 1(b).…”
Section: B1 Simulation Studymentioning
confidence: 99%
“…For the WTV approach, we used the partially sampled image reconstructed using MLEM (20 iterations) as the initialization point and iterated 150 times due to the complexity of the proposed cost function while using the steepest descent algorithm 12 to reach the global minimum. In this implementation, the α and β values were set to 0.24 and 0.63, respectively.…”
Section: B1 Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations